Association between rs174537 FADS1 polymorphism and immune cell profiles in abdominal and femoral subcutaneous adipose tissue: an exploratory study in adults with obesity. (1st January 2021) - Wang, Chenxuan; Murphy, Jessica; Delaney, Kerri Z.; Khor, Natalie; Morais, José A.; Tsoukas, Michael A.; Lowry, Dana E.; Mutch, David M.; Santosa, Sylvia
ABSTRACT: Fatty acid desaturase 1 ( FADS1 ) polymorphisms alter fatty acid content in subcutaneous adipose tissue (SAT); however, existing evidence is limited and conflicting regarding the association between FADS1 variants and SAT inflammatory status. To advance this area, we conducted an exploratory study to investigate whether the common rs174537 polymorphism in FADS1 was associated with immune cell profiles in abdominal and femoral SAT in individuals with obesity. FADS1 gene expression and immune cell profiles in SAT depots were assessed by qPCR and flow cytometry, respectively. Although FADS1 gene expression was associated with genotype, no associations were observed with immune cell profiles in either depot. Our study provides additional evidence that rs174537 in FADS1 has minimal impact on inflammatory status in obese SAT.